2017
DOI: 10.1016/j.bbmt.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-Host Disease of the Gut: A Histologic Activity Grading System and Validation

Abstract: The pathologic interpretation of gut biopsies in hematopoietic cell transplant recipients to assess graft-versus-disease (GVHD) is well accepted and supplements clinical and endoscopic findings. However, the histologic activity grading of GVHD is controversial, with attempts to predict prognosis or response to treatment largely unsuccessful. GVHD is being diagnosed earlier in its course, raising the possibility that the pathologic grading system can be profitably modified. We have developed a histologic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…A limited study by Nguyen et al 37 suggested that even a single apoptotic body per total biopsy (all pieces in aggregate) might suffice for a diagnosis of GI GVHD in some circumstances. Recently, the use of a low threshold was further supported in a study by Myerson, et al, 38 which validated the use of a modified Lerner grading system for GVHD that essentially subdivided the former grade 1 into 4 new grades and combined grades 2 to 4 in a new grade 5. Within their cohort, a diagnosis of their proposed grade 1 or grade 2 GVHD (!0.07 to ,0.25 apoptotic bodies and !0.25 to ,4 apoptotic bodies per section, respectively) often still led to treatment for GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited study by Nguyen et al 37 suggested that even a single apoptotic body per total biopsy (all pieces in aggregate) might suffice for a diagnosis of GI GVHD in some circumstances. Recently, the use of a low threshold was further supported in a study by Myerson, et al, 38 which validated the use of a modified Lerner grading system for GVHD that essentially subdivided the former grade 1 into 4 new grades and combined grades 2 to 4 in a new grade 5. Within their cohort, a diagnosis of their proposed grade 1 or grade 2 GVHD (!0.07 to ,0.25 apoptotic bodies and !0.25 to ,4 apoptotic bodies per section, respectively) often still led to treatment for GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Translating those numbers into the typical biopsy piece that contains approximately 20 glands or crypts equates to 0.4 to 1 apoptotic body per biopsy piece, a range bordering the NIH guideline recommendation for GI GVHD. 38 Perhaps in recognition of the low but significant baseline level of apoptosis, Lin et al 42 have suggested the use of criteria for the histologic diagnosis of GI GVHD similar to those employed for acute cellular allograft rejection of small-bowel transplants, with 6 or more apoptotic bodies per 10 contiguous crypts required for a diagnosis of GVHD and biopsies falling short of that criterion being designated indeterminate. Although that approach would undoubtedly decrease the frequency of FP diagnoses, it would clearly lead to a decrease, possibly to an unacceptable level, in diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…An epithelial cell apoptotic body was defined using the criteria outlined by Myerson et al 7. In the first arm of the study, the following data were recorded for each specimen: the number of biopsies and serial sections, and the number of apoptotic bodies across all the biopsies for each serial section (starting from the most superficial section to the deepest).…”
Section: Methodsmentioning
confidence: 99%
“…16,17 COMENTARIO ANATOMOPATOLÓGICO La paciente tuvo enfermedad de injerto contra huésped en fase aguda grado histológico IV, que afectó la piel, esófago, hígado e intestino delgado. [18][19][20] Las alteraciones en la piel estaban representadas por erupción roja maculopapular generalizada; la biopsia mostró células disqueratósicas en la epidermis y en las muestras postmortem de la piel del tórax se observaron ampollas subepidérmicas (grado histológico IV, según la clasificación de Lerner). 21 En el hígado, los cambios estuvieron representados por hepatomegalia congestiva (410 vs 277 g), con tinte verdoso difuso puntiforme.…”
Section: Gerardo López Hernándezunclassified